Faktor-Faktor yang Mendukung dan Menghambat Perkembangan Kerajaan Allah di Indonesia - Krista Nessa; Nabylla Aprilia; Sarmauli Sarmauli (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This research is motivated by the importance of understanding the development of the Kingdom of God in Indonesia as a reality present in the lives of the people through the values ​​of love, justice, and peace in a pluralistic society. The purpose of this research is to analyze the factors that support and hinder the development of the Kingdom of God in Indonesia and explain its application in contemporary life. The method used is a qualitative descriptive method through a literature review and theological analysis of the social, cultural, and religious dynamics that are developing in Indonesian society. The results of the study indicate that the development of the Kingdom of God is supported by the role of the church in evangelistic missions, holistic services, universal values ​​of love and justice, and a spirit of religious moderation. On the other hand, this development is hampered by local cultural resistance, socio-political dynamics, a lack of comprehensive theological understanding, and the potential for conflict in poorly managed plurality. The implications of this research emphasize that the Kingdom of God needs to be lived as a contemporary reality through personal and social transformation, obedience to God's will, and the realization of identity as citizens of the Kingdom of God in everyday life.